THE INFLUENCE OF SMART TECHNOLOGIES ADOPTION IN ENHANCING PORT EFFICIENCY: A CASE OF DAR ES SALAAM SEAPORT - Chaula, William; Luambano, Hans (Journal of Industrial Engineering & Management Research, 2025)
Smart technologies are transforming port operations worldwide by improving speed, accuracy, security, and environmental performance. This paper examines the influence of smart technology adoption on operational efficiency at the Dar es Salaam seaport, focusing on three components: system automation, real-time data integration, and cybersecurity. Guided by the Theory of Technology Dominance and employing a positivist quantitative approach, the study uses descriptive research design and analyzes data collected from port management, shipping companies, and shipping agents. A sample of 95 respondents provided primary data via structured questionnaires; secondary sources included port reports and scholarly literature. Descriptive statistics, Pearson correlations, and multiple regression analyses were computed using SPSS v.30. Results indicate that automation has the strongest positive effect on port efficiency, followed by cybersecurity. Real-time data integration shows a positive but marginally insignificant effect.The combined model explains approximately 40.5% of variance in operational efficiency. Findings suggest that targeted investments in automation and cybersecurity, together with improved integration of real-time data platforms, will substantially enhance performance at Dar es Salaam Seaport . The paper concludes with policy recommendations for the Tanzania Ports Authority and directions for future research.